Refleksje nad ciążą i porodem. Perspektywa krytycznej analizy dyskursu - Nowakowska, Luiza (Kultura-Społeczeństwo-Edukacja, 2014)
The topic of discussion is the discourse that shapes around pregnancy and childbirth in the past about two hundred years in Western countries – the mechanisms of its development, the most important manifestations and possible consequences. Theoretical basis for this problem is – Critical Discourse Analysis (CDA), and the main inspiration was the concept of M. Foucault – how according to the author this discourse is constructed, imposed and reproduced. „(...) in every society the production of discourse is at once controlled, selected, organized and subjected to redistribution by a number of procedures, whose role is to (...) take over the randomness of events (...)” writes Foucault. The purpose of the following discussion is, therefore, an attempt to show these „procedures” – methods and measures that are imposing and strengthen the medical discourse on pregnancy, childbirth, and more broadly the female body.